Design an Experiment Using Passive Sampling Technique for Monitoring Heavy Metals: A case study in Nhue river, Vietnam - Dao, Duy Nam; Ton, Thu Giang; Tran, Thanh Chi (Old Journal, 2019)
Passive sampling technique (Chemcatcher) was applied to monitor several heavy metals (Cd, Cu, Zn and Ni) in Nhue river (Vietnam). The components of sampler are sampler body (UK), Cellulose Acetate membrane (US) and Chelating Empore disk (UK). The effective sampling rate of the device (Rs, L·day-1) is defined as the equivalent volume of water extracted per unit time and specific analyte. Rs can be determined experimentally in a flow-through tank. Impacts of water temperature and turbulence on the uptake rate of heavy metals were investigated under controlled laboratory conditions. The results of the sampling rate (Rs) are as follows 0.0092-0.0179 L·h-1, 0.0042-0.0268 L·h-1, 0.0063-0.0231 L·h-1 and 0.0067-0.0205 L·h-1 for Cd, Cu, Zn and Ni, respectively. Two sampling points on Nhue River were selected for sampling in parallel in 24- and 72-hours field deployment. In addition, spot samples were taken to evaluate data. The Time-weighted average (TWA) water concentration is 0.023-0.045 µg/L in two sampling points for Cadmium and 16.95-62.17 µg/L, 9.74-35.71 µg/L for sampling point NM1, NM2 of Zinc, respectively. Chemcatcher sampling measures only the labile fraction of heavy metals in water.